The Factors Influencing the Prevention of Fraud in Village Fund Management Case Studies on Villages in Caringin Sub-District Bogor Regency - Sutisna, Dede; Setiawan, Ade Budi; Marsudi, Joko (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2024)
Year after year, the value of the village budget continues to increase. Unfortunately, this increasing trend is also accompanied by an increase in cases of fraud in the handling of village funds. The aim of this research is to examine the influence of HR competency, exemplary leadership, internal control systems, and violation reporting systems (whistleblowing systems) in preventing fraud in managing village funds. A quantitative approach was used for this research. The research population consisted of village officials from 12 villages in Caringin District. Sample determination was carried out using a simple random sampling method using the Slovin formula. Data collection was carried out by distributing questionnaires to 127 village officials accompanied by interviews to further strengthen the research data. Data analysis uses multiple linear regression analysis with SPSS 25 software. Research findings show that human resource competency, exemplary leadership, internal control systems, and whistleblowing system partially influence the prevention of fraud in managing village funds with a magnitude of influence or human resource competency coefficient value of 0.502, exemplary leadership at 0.094, internal control system at 0.124 and whistleblowing system at 0.163. All variables in this research also simultaneously influence the prevention of fraud in village fund management with a contribution amount of 82.8%, which means the level of influence is very strong.